Postmenopausal Osteoporosis: From Mechanisms to Modern Therapies - Lambach, Jakub; Kutnik, Kacper; Woźnica, Weronika; Matuszewska, Julia; Białogłowski, Michał; Maziarczyk, Alicja; Gęborys, Anna; Mazurek, Katarzyna; Wojcieszak, Maja; Miazga, Dominika (Quality in Sport, 2026)
Background. Osteoporosis is the most common metabolic bone disease and represents a serious public health problem, particularly among postmenopausal women. It is characterized by reduced bone mineral density and bone microarchitecture disorders, leading to an increased risk of fractures, mortality, and socioeconomic burden. Estrogens play a key role in skeletal homeostasis by regulating osteoclasts, osteoblasts, and osteocytes. Advances in research have led to the development of effective pharmacological therapies targeting bone resorption and formation. In combination with supportive measures, these therapies form the basis of individualized strategies for fracture prevention and bone health maintenance in postmenopausal women. Aim. The aim of this study is to review the role of estrogen deficiency in the pathogenesis of postmenopausal osteoporosis and to evaluate current pharmacologic treatment options, with a particular focus on their mechanisms of action, effects on bone remodeling, and efficacy in reducing fracture risk. Material and methods. We conducted a review of the literature from 2015-2025 available in the PubMed database, using the keywords “postmenopausal osteoporosis” “postmenopausal osteoporosis treatment” and “osteoporosis hormones” Results. A range of effective pharmacologic therapies is available to reduce fracture risk. Antiresorptive agents such as bisphosphonates and denosumab are central to treatment, while hormone replacement therapy and selective estrogen receptor modulators may benefit selected patients. Osteoanabolic agents are particularly valuable for individuals at high fracture risk. Calcium and vitamin D provide supportive benefits when deficiency is present. Conclusions. Personalized, long-term therapeutic strategies such using osteoanabolic agents and antiresorptive agents as are critical to preserving bone health and optimizing treatment results in postmenopausal women.